Iridoids in Hydrangeaceae. (February 2016) - Gousiadou, Chrysoula; Li, Hong-Qing; Gotfredsen, Charlotte; Jensen, Søren Rosendal
Abstract: The content of glycosides in Kirengeshoma palmata and Jamesia americana (Hydrangeaceae) have been investigated. The former contains loganin and secoiridoids, including the alkaloid demethylalangiside. The latter contains no iridoids, but the known glucosides arbutin, picein and prunasin. In order to futher investigate the chemotaxonomy of the family Hydrangeaceae, the distribution of the iridoid and secoiridoid glucosides as well as the known biosynthetic pathways to these compounds have been reviewed. However, only a few genera of the family has been investigated. Loganin, secologanin, and derivatives of these are common. The genus Deutzia is characteristic in containing more structurally simple iridoids in which C-10 has been lost during biosynthesis. Such compounds have so far only been reported from the genus Mentzelia (Loasaceae). The taxonomic relationships between Hydrangeaceae and the closely related Cornaceae and Loasaceae is discussed and found to agree well with recent DNA sequence results. Graphical abstract: Kirengeshoma and Jamesia have been investigated. The former contains loganin and secoiridoids, including the alkaloid demethylalangiside. The latter contains no iridoids, but the known glucosides arbutin, picein and prunasin. The distribution of the iridoid and secoiridoid glucosides as well as the known biosynthetic pathways to these compounds in the family Hydrangeaceae is reviewed. Highlights: In the present work Kirengeshoma and Jamesia have been investigated. 6-Hydroxysweroside and the demethylalangiside were found in Kirengeshoma . The occurrence of iridoid glucosides in the family Hydangeaceae is reviewed. The chemotaxonomy of Hydrangeaceae is discussed.